2013
DOI: 10.1136/bcr-2012-008249
|View full text |Cite
|
Sign up to set email alerts
|

The use of ozone therapy in Buruli ulcer had an excellent outcome

Abstract: This is the first case reporting the effective use of 2 weeks of ozone therapy for the treatment of Buruli ulcer (BU), a dramatic disease caused byMycobacterium ulcerans, an epidemic in central Africa. This simple and cheap treatment could become an effective option for managing BU as an alternative to antibiotic or surgical treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Such properties might potentially accelerate healing of the lesions leading to reductions of ulcer size and ulcer duration. This agreed with previous studies that applied ozone for the treatment of other types of ulcers (such as ulcers involving the stomach, duodenum, veins, and skin) and revealed that ozone was associated with better healing of the ulcers 20 21 22 23 24 25 . However, this contrasts with the findings of previous studies that applied ozone to bone and soft tissues during third molar surgery and found that it did not affect healing time but significantly reduced pain levels 28 30 31 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Such properties might potentially accelerate healing of the lesions leading to reductions of ulcer size and ulcer duration. This agreed with previous studies that applied ozone for the treatment of other types of ulcers (such as ulcers involving the stomach, duodenum, veins, and skin) and revealed that ozone was associated with better healing of the ulcers 20 21 22 23 24 25 . However, this contrasts with the findings of previous studies that applied ozone to bone and soft tissues during third molar surgery and found that it did not affect healing time but significantly reduced pain levels 28 30 31 .…”
Section: Discussionsupporting
confidence: 92%
“…The study limitations are that the size of the study sample is small; nevertheless, the sample size in this study is comparable to or even larger than the sample size in previous investigations in this field 15 18 19 20 21 22 23 24 25 . Also, pain assessment in this study depended on subjective reporting of patients’ opinions regarding pain levels.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It implies the use of a portable NPWT equipment for outpatients to promote tissue granulation growth and wound blood flow, and which can reduce edema and bacterial growth [ 6 , 85 ]. The application of ozone for the treatment of BU has successfully been tested in Central Africa, involving placing a bag over the lesion and inhaling a combination of O 2 –O 3 with a concentration of 30 g/ml [ 86 ].…”
Section: Health Systems In Africa and Implications For Bu Managementmentioning
confidence: 99%
“…When the bag is removed, the wound is covered with a sterile gauze. A case with a skin ulcer in Benin was reported to be healed after the ozone applications in 2 weeks [41]. Compared to surgical treatment, NPWT and ozone therapy are easy to use procedures.…”
Section: Other Suggested Therapiesmentioning
confidence: 99%